STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA RELIGIUS BERBASIS PEMBIASAAN SISWA DI SMAS PERMATA INSANI ISLAMIC SCHOOL - Resta Ayini; Juliana Nurajizah; Dea Puspita; Windi Yani Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the principal's leadership strategy in developing religious culture based on student habituation at SMAS Permata Insani Islamic School. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study show that the principal's leadership strategy is carried out through example, habituation of religious activities, strengthening discipline, and cooperation with teachers and parents of students. The forms of religious culture that are applied include congregational prayers, reading the Qur'an, joint prayer, and habituation of discipline and manners. The supporting factors of this study are the commitment of school residents and a conducive school environment, while the inhibiting factors include differences in student character and lack of consistency among some students in carrying out religious habits. This research shows that the leadership of school principals plays an important role in shaping a sustainable religious culture in the school environment. Keywords: Principal's Leadership, Religious Culture, Student Habituation